Continued use of poliovirus after eradication: hyper‐attenuated strains as a safe alternative for release testing of human immunoglobulins. (7th December 2018) - Farcet, Maria R.; Modrof, Jens; Rabel, Philip O.; Schirmer, Andreas; Macadam, Andrew J.; Fox, Helen; Minor, Philip D.; Kreil, Thomas R.
Abstract : BACKGROUND: Wild‐type poliovirus may be eradicated soon and under WHO GAPIII guidance, laboratory use will be discontinued or subject to strict containment. Per US Code of Federal Regulations, however, immunoglobulin lot release testing will still require use of replicating poliovirus. The suitability of S19 hyper‐attenuated and apathogenic poliovirus strains as alternatives to the currently used wild‐type virus in such a release assay was investigated. STUDY DESIGN AND METHODS: S19 poliovirus strains were propagated in a commercial setting using good virological practices and maintenance of the S19 hyper‐attenuated genotype was confirmed by massively parallel sequencing. RESULTS: The attenuated phenotype of the produced S19 stocks was confirmed in a highly sensitive mouse‐model. Equivalency in performance was seen in the lot release assay for the S19 and wild‐type polioviruses. CONCLUSION: The deployment of such hyper‐attenuated and thoroughly characterized S19 stocks in these and other essential activities might reconcile final containment measures with continued safe use of poliovirus.